Strategi Promosi Dalam Meningkatkan Daya Kunjung Wisatawan Pada Objek WiSata Rawa Cinta Kampung Nggayu - adryani, paul (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
Purpose of the study was to find out the Promotion Strategy in Increasing Tourist Visiting Power at Rawa Cinta Kampung Nggayu Tourism Object.To obtain research data, researchers interviewed 20 people as informants. The analysis data uses a descriptive method. This research uses a qualitative approach, while the data analysis technique, the author uses three stages: Data reduction, data presentation, and conclusion drawing. The results of this study show a promotional strategy, namely: rawa cinta tourism managers in determining the target audience, namely all circles of society aimed at reaching tourists widely. Rawa Cinta tourism managers in designing messages are the use of sentences based on the beauty of tourist attractions supporting facilities and tourist attractions that are easy to travel using motorized vehicles. Then the media used is based on the availability of funds, namely using social media. Print media such as brochures, posters, billboards, phamplets, and stickers are still not carried out.furthermore, As a support, in accordance with the SWOT analysis indicators, namely: strengths such as resources and very adequate advantages, namely the scenery that is still beautiful, For weaknesses in development and to add visitors to the clove swamp tourism, the main funding problems and places far from the center of keramain, The advantages of the rawa cinta tourist attraction are being in the middle of the district, so it can become a tourist center